Prescribing Pattern of Medications in Geriatric Patients in a South Indian Tertiary Care Teaching Hospital - Golla, Pavani; Bheemathati, Ranga Rao; Ramesh, Sai Pawan Adepu; Edara, Namratha; Adepu, Ramesh (Indian Journal of Pharmacy Practice)
Background: Globally, the population of elderly is gradually rising. Co-morbidities and polypharmacy are the prime reasons for the inappropriate use of medications. Objective: A prospective, observational study was conducted in a South Indian tertiary care teaching hospital to assess the medication prescribing pattern in elderly patients and also to evaluate the inappropriateness of medications using Beer’s criteria. Materials and Methods: Institutional ethics committee has approved the study. Written informed consent was taken from all the enrolled elderly patients meeting the inclusion criteria. Necessary demographic, clinical, laboratory and therapeutic information was collected and recorded in a suitably designed data collection form and the same was evaluated for prescribing pattern and inappropriateness using Beer’s criteria. Results: A total of 104 patients aged above 60 years were enrolled into the study. Among them 64 patients (61.53%) were males and 40 (38.46%) were females. Among these patients 61 (58.65%) patients were in the age group of 60-65 years, 25 (24.03%) were in 66-70 years, 12 (11.53%) were in 71-75 years, 6 (5.76%) were >75 years. Common cause for hospital admission was hypertension and diabetes. As per Beer’s criteria, 91.3% prescriptions given to the study patients were found inappropriate. Antibiotics and Pantoprazole were the most commonly prescribed drugs. The study findings suggest that use of poly pharmacy is high and majority medications prescribed were found inappropriate as per the Beer’s criteria. Conclusion: Presence of clinical pharmacist would optimize the drug therapy and minimize the drug related problems and negative therapeutic outcomes in elderly patients.
Keywords: Geriatrics; Beer’s criteria; Inappropriate medication; Polypharmacy; Irrational prescribing.